Evaluation of study plan of Anthropology Professional Career of San Marcos Major National University in the framework of University Law 30220 - Pino Apablaza, Fernando (2021)
The present educative research, was done in the first trimester of 2021. Had like objective evaluate the last version of study plan of Anthropology Professional Career at National Major San Marcos University for recommend a propose a change pertinent to new law 30220. Educative law to push the universities to modify yours curriculums and study plans every three years or in relation about the last scientific and technological advances. To evaluate the study plan, the research had like criteria, the articles in relation to curriculum design in the framework of the university law 30220 of 2014. The study plan was evaluate through the documental analyze. The results were favorable, because the plan connect with the most of criteria law.